Differential expression of desaturase genes and changes in fatty acid composition of Mortierella sp. AGED in response to environmental factors. (5th September 2016) - Tan, Li; Zhuo, Rui; Li, Shue; Ma, Fuying; Zhang, Xiaoyu
Abstract: BACKGROUND: Some oleaginous fungi can produce large amounts of polyunsaturated fatty acids (PUFAs) which serve many physiological functions. Numerous desaturases are critical for the synthesis of PUFAs. This study aimed to investigate the regulation of lipid production and desaturase gene expression in Mortierella sp. AGED in response to different environmental factors, and the relationships between lipid production and desaturase gene expression. RESULTS: The fatty acid composition and mRNA levels of desaturase genes were significantly changed under low temperatures. With the exception of Δ5‐desaturase, the transcript levels of all desaturase genes increased at a temperature of 20 °C. Changes in content of lipid and PUFAs responding to low temperature were consistent with desaturase gene expression. Time course studies on gene expression showed that mRNA levels of four desaturase genes increased rapidly after transferring the cells to low temperature. Ethanol (1.5% v/v) increased the transcript levels of Δ9‐, Δ6‐ and Δ5‐desaturase genes significantly and of Δ12‐desaturase gene slightly. Different metal ions such as Ca 2+, Zn 2+ and Fe 3+ could stimulate PUFA synthesis and up‐regulate desaturase gene transcription, while Cu 2+ inhibited desaturase gene expression and lipid accumulation. CONCLUSION: This study should enable us to understand the regulatory mechanism of desaturase gene expression and lipid synthesis. It is helpful to improve PUFA productivity in Mortierella sp. AGED. © 2016 Society of Chemical Industry